The development of an epilepsy electronic patient portal: Facilitating both patient empowerment and remote clinician‐patient interaction in a post‐COVID‐19 world. (10th August 2020) - Power, Kevin; McCrea, Zita; White, Maire; Breen, Annette; Dunleavy, Brendan; O'Donoghue, Sean; Jacquemard, Tim; Lambert, Veronica; El‐Naggar, Hany; Delanty, Norman; Doherty, Colin; Fitzsimons, Mary
Abstract: Objectives: The current coronavirus disease 2019 (COVID‐19) pandemic stresses an urgency to accelerate much‐needed health service reform. Rapid and courageous changes being made to address the immediate impact of the pandemic are demonstrating that the means and technology to enable new models of health care exist. For example, innovations such as electronic patient portals (ePortal) can facilitate (a) radical reform of outpatient care; (b) cost containment in the economically constrained aftermath of the pandemic; (c) environmental sustainability by reduction of unnecessary journeys/transport. Herein, the development of Providing Individualised Services and Care in Epilepsy (PiSCES), an ePortal to the Irish National Epilepsy Electronic Patient Record, is demonstrated. This project, which pre‐dates the COVID‐19 crisis, aims to facilitate better patient‐ and family‐centered epilepsy care. Methods: A combination of ethnographic research, document analysis, and joint application design sessions was used to elicit PiSCES requirements. From these, a specification of desired modules of functionality was established and guided the software development. Results: PiSCES functional features include "My Epilepsy Care Summary, " "My Epilepsy Care Goals, " "My Epilepsy Clinic Letters, " "Help Us Measure Your Progress, " "Prepare For Your Clinic Visit, " "Information for Your Healthcare Provider." The system provides people with epilepsy access to, and engages them as co‐authors of, their own medical record. It can promote improved patient‐clinician partnerships and facilitate patient self‐management. Significance: In the aftermath of COVID‐19, it is highly unlikely that the healthcare sector will return to a "business as usual" way of delivering services. The pandemic is expected to accelerate adoption of innovations like PiSCES. It is therefore a catalyst for change that will deliver care that is more responsive to individual patient needs and preferences.